Organizational Culture and HR Management in Public Sector: Social Exchange Mechanisms in the Merit System for Senior Official Selection in Riau Provincial Government - Ikhwan Ridwan; Oman Sukmana; Rachmad Kristiono Dwi Susilo; Junaidi Junaidi (Sharia Economic and Management Business Journal (SEMBJ), 2026)
Background: Organizational culture and HR management in public bureaucracy face a structural paradox when formal merit systems operate alongside deeply embedded socio-cultural norms. Riau Province's Civil Service Merit Index rose from 227.5 (2019) to 325.5 (2024), yet the "Promotion & Mutation" sub-componentthe direct measure of appointment integrityscored only 37.5% in the critical 2020 mass selection year. Simultaneously, 54.2% of appointments went to candidates ranked 2nd or 3rd rather than to the highest-scorer, signaling systematic non-merit intervention. Method: Qualitative case study design (Yin, 2022) examining the 2020 open selection of 24 Senior Civil Service (JPT Pratama) positions in Riau Provincial Government. Data from in-depth interviews (n=17 key informants), participant observation (8 months), and document analysis were analyzed through a thematic-dialectical procedure framed within social exchange theory (Homans, 1961; Blau, 1964; Emerson, 1976; Molm, 2003), Ekeh's Two Publics (1974), and Riau Malay organizational culture (Effendy, 2013). Results: Three simultaneous exchange layers structure the HR appointment process: (1) an administrative layer where competency scores are exchanged for procedural legitimacy; (2) a substantive back-stage layer in the governor's discretionary space where political loyalty displaces merit as the decisive currency; and (3) a cultural legitimation layer where Malay values of Berbalas Budi (reciprocal kindness), Amanah (trust), and Marwah (dignity/honor) are strategically renarrated as moral cover (Selubung Moral) to normalize patronage. Conclusion: The study proposes a Culturally Contextualized Social Exchange Model (CCSEM)a Hybrid Bureaucracy Frameworkwherein formal merit functions as institutional legitimacy scaffolding, patronage serves as the substantive appointment driver, and local culture acts as the moral adhesive sustaining this hybrid equilibrium. This contributes novel theoretical ground to organizational sociology and Islamic corporate governance, calling for reforms that reclaim authentic Islamic-Malay values against their appropriated, patronage-justifying distortions.